Foreword - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2021)
The editorial team of the Singapore Law Journal must be one of the bravest group of people around. I say this because it takes much effort to start a law journal and then sustain it thereafter. Despite knowing the immense challenges ahead, the editorial team decided to go ahead with the journal, convinced that it will be a welcome addition to academic legal literature. With their enthusiasm and energy, I have every confidence that they will succeed and that the Singapore Law Journal will become an important addition to the academic landscape.